2021
DOI: 10.1111/jsr.13500
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep pattern and dream activity across and after the COVID‐19 lockdown in Italy: A longitudinal observational study

Abstract: Summary A large body of evidence has documented the impact of the global COVID‐19 outbreak – and especially the lockdown period – on sleep quality and quantity. Here, we present the first Italian longitudinal study on sleep and COVID‐19 considering four different time points collected during lockdown (from 29 March 2020 to 3 May 2020) and a subsequent follow‐up period (October 2020). We used an online survey to collect socio‐demographic and COVID‐19 related information. Subjects were also asked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…It should be noted that we did not send reminders to the individuals after inviting them to participate in the second survey, likely limiting the number of participants. Our final percentage of respondents at the follow-up (i.e., 21.3%) is similar to other longitudinal sleep studies during the pandemic [ 9 , 34 , 83 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It should be noted that we did not send reminders to the individuals after inviting them to participate in the second survey, likely limiting the number of participants. Our final percentage of respondents at the follow-up (i.e., 21.3%) is similar to other longitudinal sleep studies during the pandemic [ 9 , 34 , 83 ].…”
Section: Discussionsupporting
confidence: 85%
“…These changes in oneiric activity co-occurred with greater ease of falling asleep and a reduced number of awakenings after the lockdown. Another Italian study [ 34 ] performed a week-by-week evaluation of sleep and dream diaries during the last period of the first TL (29 March 2020–3 May 2020), and a follow-up assessment during a post-lockdown (PL) period, characterized by eased restrictions (October 2020). Beyond reduced sleep latency, greater ease of falling asleep, and higher total bed time at the follow-up examination, an initial increase in dream frequency was observed during the TL, which remained stable until the end of the isolation period, followed by a PL reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, our results showed that the time spent at home after the lockdown was reduced, compared with the home confinement period, but it was significantly greater than the pre-lockdown period, suggesting that participants in our sample did not return to the habitual pre-pandemic daytime schedule immediately after the lockdown. It is worth noting that an Italian study found substantially stable sleep patterns during the lockdown through a week-by-week assessment of sleep diaries, followed by a reduction in sleep onset latency, time in bed, and dream frequency and an increase in the perceived ease to fall asleep 4 months after the end of the lockdown [ 36 ]. Therefore, it is possible that a longer period of time in a condition of relative stability and a further reduction in the restrictions are needed to observe major changes in sleep quality after the end of home confinement.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review estimated that the prevalence of sleep problems during the COVID-19 pandemic was high and affected approximately 40% of people from general and health care populations [18]. A longitudinal study observed longer sleep latency, worse sleep efficiency, and massive sleep medication use, but an increased sleep duration and better daytime functioning, in Italian participants during the COVID-19 lockdown [19,20]. Moreover, the increase in sleep difficulties was associated with higher levels of depression, anxiety, and stress among Italian adults during the lockdown [21].…”
Section: Introductionmentioning
confidence: 99%